PELATIHAN LEADERSHIP LIFE SKILL DAN PERENCANAAN DESAIN KONSEP DALAM MEMPERSIAPKAN WIRAUSAHA BAGI SISWA SMA - Ahmad; Raviva, Aifa; Sp, Tharisya (Jurnal Serina Abdimas, 2023)
This training provides an introduction related to leadership and design thinking for high school students so that they have leadership skills and creativity in making decisions, especially in starting to capture consumer needs and then decide to become a new business to be developed. Someone is considered to have good leadership skills if they have attitudes such as social skills, have wisdom and courage and are able to make good decisions about the problems they face. Leadership is the key to business success in achieving goals. Realizing consumer needs requires creativity and knowledge about design and its aspects, such as ergonomic and aesthetic aspects which are usually required for several products. The aim of the training is for participants to be able to capture business opportunities to be developed and have good leadership skills in making decisions. The method used in this PKM is in the form of lectures, where the training material is given accompanied by examples so that participants understand it well. From the results of the final questionnaire on the results of the training, it was found that 76% of the participants considered that the benefits of this training were very good. Pelatihan ini memberikan pengenalan berkaitan dengan leadership dan desain thinking pada siswa SMA agar memiliki skill leadership dan kreativitas dalam mengambil keputusan, khususnya dalam memulai menangkap kebutuhan konsumen kemudian memutuskan menjadi sebuah usaha baru yang akan dikembangkan. Seseorang dianggap memiliki skill leadership yang baik jika memiliki Sikap seperti keterampilan sosial, memiliki Kebijaksanaan dan keberanian serta sanggup memutuskan dengan baik terhadap masalah yang dihadapi. Leadership adalah kunci keberhasilan usaha dalam mencapai tujuan. Dalam mewujudkan kebutuhan konsumen dibutuhkan kreatifitas dan pengetahuan tentang desain dan aspek-aspeknya, seperti aspek ergonomis dan estetika yang biasanya dibutuhkan pada beberapa produk. Tujuan dari pelatihan agar peserta mampu menangkap peluang usaha untuk dikembangkan serta memiliki kemampuan leadership yang baik dalam mengambil keputusan. Metode yang dipakai dalam PKM ini dalam bentuk ceramah, dimana materi pelatihan diberikan disertai dengan contoh-contoh sehingga peserta memahami dengan baik. Dari hasil kuesioner akhir terhadap hasil pelatihan diketahui 76% peserta menilai bahwa manfaat dari pelatihan ini sangat baik.